Tax and sustainable development in sub-Saharan Africa: Beyond accountability and responsiveness - Alex Adegboye; Abrams M. E. Tagem (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper establishes how accountability quality might mediate the effect of tax revenue on sustainable development in 41 sub-Saharan African countries for the period 1990-2019. The empirical evidence is based on three empirical strategies: generalized method of moments, instrumental variable Tobit, and quantile regressions. The following findings are revealed. First, accountability dynamics influence tax revenue in ways that have favourable net effects on sustainable development. Second, the conditional impacts between accountability dynamics and tax revenues are constantly negative, even though the demonstrated net effects are compatible with the paper's theoretical predictions. Third, the net consequences are decomposed to establish thresholds for further policy. Thresholds are points where there are no net effects and where further intensifying accountability dynamics would produce adverse net impacts. At the stated thresholds, further policy actions must be complemented with accountability dynamics in order to modulate tax revenues for strong sustainability. We conclude that policy makers in sub-Saharan African nations should coordinate measures that improve accountability in view of other complementary policies, because accountability serves as a 'force multiplier' enhancing the absorptive capacity of tax mobilization, which in turn promotes strong sustainability.
Keywords: J18; H20; O11; 330; sub-Saharan Africa; accountability quality; tax mobilization; sustainable development